Plasma rico em plaquetas: obtenção, momento de produção e uso na integração de flapes cutâneos de avanço em cães - CAVALCANTI, Grazielle Anahy de Sousa Aleixo (2010)
A lot of emphasis has been given to the use of platelet rich plasma (PRP) in various areas of medicine, including reconstructive surgery, because when it is applied on a tissue in repair its capable of stimulating many important cellular processes, such as proliferation,differentiation, chemotaxis and angiogenesis. The aim of this paper was to evaluate the PRP effects over integration of advance skin flaps in dogs. In the first stage of the research, blood samples were collected from 20 dogs to compare two protocols used to obtain PRP. In the first protocol (A), blood sample was submitted to a single spin at 1200 revolutions per minute (rpm) for 10 minutes while in the second protocol (B), the sample was processed through two centrifugations, the first at 1200 rpm for 10 minutes and the second at 1600 rpm for 10 minutes. The results showed that protocol B was able to increase platelet count in 449,02% compared to whole blood, being higher than protocol A (190,22%). In the sequence, protocol B was applied in other 20 animals to evaluate its efficiency and it was found that the methodwas reproducible. After that, blood samples from 20 dogs were collected for production of PRP at two different moments: M0, corresponding to preoperative time, before anesthesia and fluid therapy, and M1, during trans-surgical period, after anesthesia. Platelets counts of blood collected in M0 were 28,58% higher than in M1, leading consequently, to the production of a more concentrated PRP. After defining the best protocol (B) and the ideal moment to collect the blood sample (M0) began the final stage of the experiment, in which two advance flaps were created in the ventral abdomen of eight dogs. Between one flap and recipient bed, PRP gel activated with thromboplastin was applied, whereas under the other flap was not applied any product(control). The flaps were clinically evaluated 24 hours after surgery (D1) and at every two days (D3, D5 and D7) until the seventh day after surgery. With ten days, both flaps were removed for histopathological examination and morphometry of blood vessels where it was demonstrated no significant difference between treated and control flap. Based on the results, it is concluded that platelet gel activated with thromboplastin did not enhance integration of advance skin flaps in dogs.